2015
DOI: 10.4172/2167-0420.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Uterocutaneous Fistula

Abstract: Uterocutaneous fistula, although not exceptional, is a very rare clinical entity. It occurs most often after uterine or pelvic surgery. We report a case of Uterocutaneous fistula which was formed following lower segment caesarean section. MRI was helpful in the diagnosis and was treated successfully with hysterectomy. This report aims to remind practicing clinicians about this rare complication of caesarean section and discuss our experience with its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Fistulography and hysterosalpingography define the fistulous tract but cannot provide details of its communication with the other intra-abdominal viscera (1,3) . CT imaging helps in the proper delineation of the tract after the injection of the contrast agent through the abdominal site, but soft tissue resolution of CT scans is less compared with MRI (10,11) . MRI provides good soft tissue resolution, avoids radiation (as all other investigations involve significant radiation doses), and helps in proper delineation of the fistulous tract and its relation to the surrounding viscera.…”
Section: Discussionmentioning
confidence: 99%
“…Fistulography and hysterosalpingography define the fistulous tract but cannot provide details of its communication with the other intra-abdominal viscera (1,3) . CT imaging helps in the proper delineation of the tract after the injection of the contrast agent through the abdominal site, but soft tissue resolution of CT scans is less compared with MRI (10,11) . MRI provides good soft tissue resolution, avoids radiation (as all other investigations involve significant radiation doses), and helps in proper delineation of the fistulous tract and its relation to the surrounding viscera.…”
Section: Discussionmentioning
confidence: 99%
“…One should suspect this entity in a postoperative case if there is persistent discharge from scar site despite treatment, and later with regularization of periods cyclical discharge from the scar site corresponding to menstrual bleeding [1][2][3][4][5]. Vellanki et al reported a case where patient presented with groin sinus, recurrent painful swelling over edge of scar site after LSCS and was managed on lines of suture granuloma, scar endometrioma, underwent local drainage and excision but there was no relief in symptoms [7]. The diagnosis was made only after she was taken up for laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…With wide spread availability of contrast MRI scan and hysteroscopy complete delineation of fistulous tract and demonstration of its opening in uterus is used to confirm the diagnosis [9]. However, other modalities such as fistulography, hysterosalpingography, CT scan have been used for confirming the diagnosis and delineating the fistulous tract [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…An uterocutaneous fistula (communication between uterus and skin) is a rare condition, and there are only a few reports in this regard in the existing literature of its occurrence following cesarean section. Previous reports following cesarean section are associated with red degeneration of intramural fibroids, B-lynch sutures or multiple surgeries or insertion of drains or multi-associations [1,[3][4][5][6]. It has also been reported following criminal abortion [7].…”
Section: Introductionmentioning
confidence: 99%